Left ventricular diastolic dysfunction and diseases severity contribute to impaired exercise capacity in systemic lupus erythematosus - Ciurzyński, Michał; Chrzanowska, Anna; Bienias, Piotr; Domienik-Karłowicz, Justyna; Sobieraj, Piotr; Dąbrowska, Katarzyna; Dudzik-Niewiadomska, Iwona; Kurnicka, Katarzyna; Kisiel, Bartłomiej; Pruszczyk, Piotr (Lupus, 2021)
Objectives Patients with systemic lupus erythematosus (SLE) have a higher risk of myocardial involvement, which can result in ventricular dysfunction. The aim of our study was to estimate potential relationship between exercise capacity assessed by six minute walk test (6MWT) and echocardiographic parameters of left and right ventricular function in SLE patients. Methods We prospectively studied 66 SLE patients (57 F, age 44 (20–75) years) and 27 age matched healthy subjects. In addition to routine evaluation, 6MWT and transthoracic echocardiography including LV diastolic dysfunction parameters (E/A, E/É) were performed. Results While E/A was similar in both groups, E/E’ was higher in patients with SLE than in controls, 7.5 (4–22) vs 6.8 (1.6–9.4), p = 0.018. The mean 6MWT distance was significantly shorter in SLE (561.6 ± 150.7 vs 682.6 ± 98.1 m, p < 0.002). Among SLE patients only 53 (80.3%) were capable to walk at least 450 m, while in controls 27 (100%) (p = 0.013). We observed significant correlations between 6MWT distance and SLICC/ACR-DI (rho=−0.44, p < 0.001), E/A (rho = 0.30, p = 0.004), E/E’ (rho=−0.36, p < 0.001) in SLE patients. Univariable logistic regression models revealed that SLICC/ACR-DI, E/E’, tricuspid regurgitant peak gradient (TRPG), and right ventricular systolic pressure (RVSP) were associated with 6MWT distance lower than < 450 m. ROC curves shown high predictive value of E/E’ ratio, TRPG, RVSP in the prediction for 6MWT distance < 450 m. Conclusion Impaired exercise tolerance seems to result mainly from the severity of SLE and LV diastolic dysfunction.